Leucodistrofias de início na vida adulta: caracterização clínica, molecular e de neuroimagem - Nóbrega, Paulo Ribeiro (2023)
Leukodystrophies (LD) or genetic leukoencephalopathies (LG) correspond to a group of genetic diseases that compromise the white matter of the central nervous system and manifest in various ways depending on the affected regions. Neuropsychiatric disturbances, motor deficits, and incoordination are among the most common symptoms. These diseases are more common and extensively studied in childhood. The study of adult-onset leukodystrophies has recently gained relevance as a differential diagnosis of white matter lesions. Some of these diseases can even be treated. The present thesis aims to describe the clinical, laboratory, and neuroimaging aspects of patients with adult-onset leukodystrophy, identify characteristics in the neurological examination and neuroimaging that facilitate their specific etiological definition, and describe new variants or possible expansions of phenotype that may be observed. Methods: This was a retrospective, descriptive, and observational study in humans, with data collection from January 2021 to March 2023. Patients with a suspected diagnosis of leukoencephalopathy were referred to the study team and evaluated clinically and laboratory. Those whose results were positive for pathogenic variants in genes involved in leukodystrophies were followed and included in the study. Clinical history and physical evaluation were performed and a standardized questionnaire in RedCap was completed. Magnetic resonance imaging examinations were evaluated by the principal investigator with the assistance of participating neuroradiologists. The project was approved by the Research Ethics Committee (REC) under Opinion No. 51404621.5.0000.5045. All patients signed an informed consent form (ICF). Results: Twenty-four patients with imaging findings compatible with the hypothesis of leukodystrophy were evaluated. In 4 patients, leukodystrophy panels were negative, and exome (WES) was negative in one patient. The diagnostic suspicion of LD/LG was confirmed in 19 patients, of whom 68% were female. The most frequent diseases were autosomal recessive (4 patients with cerebrotendinous xanthomatosis, 4 with LAMA2- related leukoencephalopathy, 3 with CLCN2-related leukoencephalopathy and ataxia, 2 with vanishing white matter disease, and 1 with Nasu-Hakola), followed by X-linked (4 patients with Fabry disease and 1 patient with X-linked adrenoleukodystrophy/adrenomyeloneuropathy). Based on the most common diseases in this case series, we published a review article on cerebrotendinous xanthomatosis, a case series with a new mutation and phenotypic expansion in Fabry disease and a case series with phenotypic expansion in CLCN2-related leukoencephalopathy and ataxia. Discussion: Knowledge of the main etiologies of adult-onset leukodystrophies should allow for better diagnosis, genetic counseling, and, in some cases, even guide specific treatment. We described the spectrum of clinical, neuroradiological, and, whenever possible, genetic manifestations of patients with LD/LG. These descriptions resulted in some review articles and others reporting new variants and/or expansions of phenotypes. The three most representative works among them were presented and discussed in this thesis.